The Role of Owners in Engineering Construction Project Management - Niu, Yanchun (Journal of Theory and Practice of Contemporary Education, 2023)
Owner project management plays an important role in managing construction projects. As an important part of construction project management, it is necessary to promptly contact relevant owners and make corresponding adjustments during construction. This is beneficial for the organization and task arrangement of the project, in order to assist in the scientific and effective management of the construction project. It not only ensures the quality of the project, but also reduces the cost of the facility construction process, and meets the requirements proposed by the owner. However, in the practical application process, the project management of the owner plays an important role in engineering project management, therefore, a relatively scientific management method must be adopted. Only in this way can the management of construction projects in engineering construction be further improved. This is mainly a comprehensive analysis and research on the engineering construction project management of the owner, hoping to provide helpful information for professionals in the same industry.